Avaliação da confiabilidade analítica das determinações de carbono orgânico total (COT) - Fonseca, J. C.L. [UNESP]; Silva, M. R.A. [UNESP]; Bautitz, I. R. [UNESP]; Nogueira, R. F.P. [UNESP]; Marchi, M. R.R. [UNESP] (Ecletica Quimica, 2006)
Observing the literature an increasing number of works can be verified that determine potential contaminants that can be present in matrices of environmental interest. It is important to stand out that when studying the environment, the analytical data are one of the tools used to evaluate the extension of the observed problems that consequently influence a decision. Thus the reliability of these data is of extreme importance. In this context, this work aims to evaluate the analytical reliability of the Total organic Carbon (TOC) determination, a tool used in the monitoring of organic substances in diverse ambient studies. For this evaluation some parameters of performance had been analyzed as limit of detection and quantification, repeatability and linearity.
Keywords: Linearity; Repeatability; TOC; Validation